A Complex Web: Access to Justice for Abused Immigrant Women in New Brunswick - Miedema, Bauje; Wachholz, Sandra (Review of Women's Studies, 2002)
Forty-eight women from diverse countries of origin participated in six focus groups. All described their social life as deeply rooted in patriarchal structures reflecting systematic patterns of male dominance. Most of them identified the interplay of cultural norms and structural oppression as profound barriers to the justice system for abused immigrant women. Structural constraints such as language barriers, perceived racism in the criminal justice system and social agencies, and lack of adequate ethnocultural services and representations were identified as disincentives to seeking help in cases of abuse. Most of the women also stated that a lack of knowledge regarding criminal and civil legal protection in cases of abuse also serves as a disincentive to contacting the justice system. The paper has recommendations on how to improve access to the criminal justice system and justice-related services as well as on how to improve awareness of socio-legal issues pertaining to women abuse and the criminal justice system.